In vitro expression of SARS coronavirus (SARS-CoV) nucleocapsid protein and examination of the function of monoclonal antibody induced by the expressed protein - CHEN Hong-xun; YAN Xing-cheng; YING Jian-yue; WU Jian-xiang; ZHOU Ji-yong (浙江大学学报. 农业与生命科学版, 2005)
To efficiently express SARS coronavirus (SARS-CoV) nucleocapsid (N) protein in vitro and produce monoclonal antibody (mAb) against SARS-CoV N protein, the recombinant clone PGEX-4T/N was induced with IPTG to express target protein and the fusion protein (GST-N) reacted specifically with anti-GST polyclonal antibody. The expressed recombinant protein was purified by affinity chromatography and gel extraction, where the purified protein concentrations were 0.85 mg/mL and 0.433 mg/mL respectively. Four hybridoma cell lines secreting monoclonal antibody (mAb) against SARS-CoV N protein were obtained and named as 3E5, 6B9, 4C2, 4B7. Subtype analysis revealed that mAbs 3E5, 4C2 and 4B7 against SARS-CoV N protein belong to IgG1 while 6B9 is allied to IgG2a. Western blot analysis showed that the four mAbs could react with SARS-CoV N protein but not with N protein of infectious bronchitis virus.